Approaches and Methods of Education Policy Analysis - Hilman, Ahmad; Rahman, Adun; Widan, Dian; Rojibillah, Isnan; Zaqiah, Qiqi Yuliati (Civiliza Publishing, Indonesia., 2025)
Educational policy analysis is a systematic process aimed at understanding, evaluating, and providing recommendations on policies related to the education system and its practices. This article seeks to elaborate on various approaches and methods used in educational policy analysis and their relevance within the context of educational development in Indonesia. The approaches discussed include normative, empirical, and critical approaches, each offering a distinct perspective in assessing policy. The analytical methods employed encompass descriptive, comparative, and evaluative analyses, as well as quantitative and qualitative data-based approaches. This study emphasizes that the effectiveness of educational policy analysis largely depends on the researcher’s ability to integrate theoretical approaches with accurate empirical data. Therefore, educational policy analysis functions not only as an evaluation tool but also as a strategic instrument in formulating policies that are more responsive, inclusive, and equitable. The findings are expected to enrich academic discourse and policy practices, particularly in efforts to improve the quality and equity of national education.